The Synthesis and Antitumor Activity of 1,8-Naphthalimide Derivatives Linked 1,2,3-Triazole - Xu, Zhong-jie; Zhou, Ying-jie; Wang, Jia-hao; Mao, Long-fei; Li, Wei; Xu, Gui-qing (Frontiers in Bioengineering and Biotechnology, 2021)
In this study, acenaphthylene was used as the raw material, and a series of novel 1,8-naphthalimide-1,2,3-triazole derivatives was obtained through oxidation, acylation, alkylation, and click reactions, and subsequently, their anti-tumor activities were tested. After screening, we found that Compound 5e showed good activity against H1975 lung cancer cells, with the half maximal inhibitory concentration (IC50) reaching 16.56 μM.